2007
DOI: 10.1038/sj.bjc.6603897
|View full text |Cite
|
Sign up to set email alerts
|

The GRAIDS Trial: a cluster randomised controlled trial of computer decision support for the management of familial cancer risk in primary care

Abstract: The objective was to evaluate the effect of an assessment strategy using the computer decision support system (the GRAIDS software), on the management of familial cancer risk in British general practice in comparison with best current practice. The design included cluster randomised controlled trial, and involved forty-five general practice teams in East Anglia, UK. Randomised to GRAIDS (Genetic Risk Assessment on the Internet with Decision Support) support (intervention n ¼ 23) or comparison (n ¼ 22). Trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
114
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(114 citation statements)
references
References 30 publications
0
114
0
Order By: Relevance
“…13 Studies in the United Kingdom have shown that referral guidelines and computerized decision support for general practitioners around familial risk assessment have facilitated appropriate referrals for genetic testing and improved clinician satisfaction with their ability to identify patients for genetic testing and manage familiar cancer risk. [30][31][32] A shortage of adult medical geneticists is another problem that has been reported. 27,33 Our study has important clinical and policy implications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Studies in the United Kingdom have shown that referral guidelines and computerized decision support for general practitioners around familial risk assessment have facilitated appropriate referrals for genetic testing and improved clinician satisfaction with their ability to identify patients for genetic testing and manage familiar cancer risk. [30][31][32] A shortage of adult medical geneticists is another problem that has been reported. 27,33 Our study has important clinical and policy implications.…”
Section: Discussionmentioning
confidence: 99%
“…2 Computerized tools that collect family history data and utilize clinical decision support to help physicians evaluate risk, provide tailored prevention messages, and make appropriate referrals may be particularly useful. 4,6,31,35,36 A major strength of our study is the use of a large, nationally representative dataset. The 2005 NHIS collected detailed information on family history of cancer, including both number of first-degree relatives and age of onset, allowing us to examine strength of familial risk in relation to awareness, referral, and use of genetic testing.…”
Section: Discussionmentioning
confidence: 99%
“…The emerging model can be supported by information technology and software applications assisting in genetic risk assessment 4,5 or by embedding genetic nurse coordinators or genetic counselors within clinics. 6,7 The traditional model of multidisciplinary specialist clinics is generally organized as a regional genetic center, usually affiliated with an academic medical center, offering clinics for various patient-care needs (e.g., prenatal, cancer genetic, and pediatric genetic needs).…”
mentioning
confidence: 99%
“…Computer aided decision making is used to improve the quality of diagnose and treatment. Emery et al 5 report an assessment strategy on British general practice familial cancer risk managing using the computer decision support system. They also reveal a computerized decision support system Risk Assessment in Genetics 6 .…”
Section: Discussionmentioning
confidence: 99%